Profitability and yield gap analysis of Binadhan-14 in some selected areas of Bangladesh - Sarkar, M M A; Rahman, M H; Islam, S; Sultana, R (Bangladesh Journal of Nuclear Agriculture, 2025)
The aim of this study was to estimate the profitability and yield gap of Binadhan-14 and to suggest some policy guidelines to minimize the yield gap. The study was conducted in Mymensingh, Jamalpur, Rangpur and Sunamganj districts of Bangladesh. Data were collected using a simple random sampling technique from 200 Binadhan-14 cultivating farmers. Data were collected through pre-designed interview schedule from October-November, 2021 for achieving the purpose. Descriptive statistics techniques as well as Stochastic Frontier model were used to achieve the objectives of the study. The average actual farmer’s yield of Binadhan-14 was 5.11 t ha-1. BCR was estimated at 1.53 implying that the Binadhan-14 cultivation at farm level was profitable. The estimated average yield gap-I was 0.43 t ha-1 (6.95 %.) and average yield gap-II was 0.71 t ha-1(12.10 %.). The average yield gap was 1.14 t ha-1 (19.05%). The farmers among the study areas did not consider the recommended doses of seed rate and fertilizers. The regression coefficients for power tiller, human labor, fertilizers, irrigation, wedding, insecticides and seed for Binadhan-14 under all areas were positive and significant at 1%, 5% and 10% level which indicated that using more of these inputs in Binadhan-14 production could increase the yield to some extent. Farmers' characteristics like age, farming experience and agricultural training found negatively related to their yield gap of the Binadhan-14. Absence of proper knowledge about the optimum input use and lack of institutional training as well as inadequate extension services were responsible for the reduced yield in most farmers’ fields. The government should realize that yield gap exists in rice crops of Bangladesh and, therefore, explore the scope to increase production as well as productivity of rice by narrowing the yield gap and thereby ensure food security. Bangladesh J. Nuclear Agric, 38(2): 111-123, 2024